Structure of genetic diversity among common bean landraces of middle American origin based on correspondence analysis of RAPD - Beebe, Stephen E.; Skroch, Paul W.; Tohme, Joseph M.; Duque E., Myriam Cristina; Pedraza García, Fabio; Nienhuis, James (Wiley, 2000)
More than 60% of common bean production worldwide is derived from cultivars of Middle American origin. Understanding the diversity of these will facilitate their use in genetic improvement. The objective of this study was to analyze a collection of 269 landraces of common bean (Phaseolus vulgaris L.) by correspondence analysis of random amplified polymorphic DNA (RAPD) data to determine the genetic structure of the Middle American gene pool of cultivated bean. One hundred eighty landraces originating in Mexico, the remainder in Central America and secondary centers of diversity within the Americas, and two checks were studied. DNA was extracted, RAPD reactions carried out, and polymorphic bands were scored as present or absent on the basis of 39 primers. Groups were formed which in part corresponded to races defined previously by morphological and agroecological criteria. However, tropical small-seeded Race M was composed of two groups: one largely Mexican that included most small-seeded black beans of upright plant habit; and one Central American with landraces of various seed colors. Most non-black small-seeded germplasm of Race M phenotype from secondary centers grouped with the Central American landraces, except for cream-seeded and purple-seeded accessions from Brazil. Races D and J could be distinguished and within races D and J further divisions could be recognized which were related to geographic origin. The more commercial Race D landraces formed a genetic group that was predominant in the western part of the Mexican highland plateau. Another Race D group was concentrated at the eastern extreme of the neovolcanic axis and was differentiated morphologically as well. Guatemalan germplasm contained accessions of climbing bean that did not group with any of the previously defined races and should be considered a separate race. Thus, Middle American germplasm of common bean is more complex than previously thought, and contains diversity that remains to be explored for its practical value.